Higher education leadership : pathways and insights - Ferris, Sharmila Pixy; Waldron, Kathleen (Studies in educational administration., 2021)
Higher education today is facing profound and unprecedented changes to which leaders must respond effectively. Offering a unique insider view of higher education, Ferris and Waldron skillfully showcase expert leadership, providing a rich and meaningful understanding of higher education leadership from across the nexus of existential, philosophical and practical concerns. Including pathways, insights and strategies developed from well-designed ethnographic research, this book incorporates twenty interviews with experienced leaders at a range of four year and doctoral granting institutions across the United States. The authors utilize phenomenological analysis to reveal nuanced elements of leadership that can help higher education leaders navigate challenges and opportunities, and respond skillfully even to the unforeseen challenges such as the Covid-19 pandemic. Bringing together a rich body of reflections, insights and experience from seasoned leaders across a wide range of applied scenarios and contexts, this book serves as a must-have reference for established and aspiring leaders who find themselves navigating new paths and challenges.